Factores asociados a la recurrencia de las fracturas vertebrales tras una vertebroplastia en el adulto mayor - Kurtz Goritz, Hugo Joel; Benolol, Leonardo Facundo; Mazzeo, Juan Jesus; Angeramo, Cristian Agustín; Eyheremendy , Eduardo P. (Revista de la Asociación Argentina de Ortopedia y Traumatología, 2026)
Introduction: Osteoporotic vertebral fractures are a common cause of morbidity in older adults. Identifying risk factors for refracture is crucial to prevent complications. Objective: To evaluate clinical and imaging variables associated with vertebral refracture after vertebroplasty. Materials and Methods: An observational study was conducted including a consecutive series of patients who underwent vertebral cementation between 2017 and 2024. The cohort was divided into two groups according to the presence (refracture group, RG) or absence (non-refracture group, NRG) of refracture within two years, defined as a new fracture in either of the two vertebrae adjacent above or below the treated level. Clinical, surgical, and imaging variables were compared. Bone density was assessed using the mean Hounsfield units (HU) of the adjacent vertebrae. Results: A total of 118 patients were included (RG: 80; NRG: 38). No significant differences were observed in age, sex, or comorbidities between groups. A history of osteoporotic fracture was more frequent in the RG (42.67% vs. 21.62%, p = 0.03). The number of fractured vertebrae was higher in the RG (2 vs. 1, p = 0.005). Bone density below the treated vertebra was significantly lower in the RG (70 HU vs. 95.69 HU, p = 0.001). In multivariate analysis, lower bone density was the only independent predictor of refracture (OR 0.98; 95%CI 0.96–0.99). The median refracture-free interval was 12 months. Conclusion: Lower bone density in the vertebrae adjacent below the treated level is associated with a higher risk of vertebral refracture.